Design of a computerized educational material for teaching of oscillations and waves, from students learning style (2018)
This paper shows the design of a computerized educational material for the teaching of oscillations and waves, aimed to high school students. It is carried out with 27 students of eleventh grade of the Institucion Técnica Educativa Valentin Garcia de Labranzagrande, Boyacá. The technological tool was designed having in mind the socio-demographic characteristics of the population, access to technology and the ability to use it. Furthermore, students learning styles were considered as a basic input to develop an appropriate material to their context. The design is based on the methodology proposed by Galvis Panqueva for the development of software, getting as a result a multimodal tool, in which different activities that focus on learning styles are presented. The proposed material includes a main menu with six themes, which incorporate activities and information related to the natural sciences subject, emphasizing on oscillations and waves topics.